A practical guide to quantum machine learning and quantum optimisation : hands-on primer to quantum computing - from qubits to quantum machine learning and beyond /: hands-on primer to quantum computing - from qubits to quantum machine learning and beyond. (2023) - Alvarez, Elias Fernandez-Combarro; Castillo, Samuel Gonzalez
No abstract available